Biological functions of compounds from Bacillus subtilis and its subspecies, Bacillus subtilis natto. Issue 3 (7th December 2022) - Miyazawa, Taiki; Abe, Chizumi; Bhaswant, Maharshi; Ikeda, Ryoichi; Higuchi, Ohki; Miyazawa, Teruo
Abstract: Natto, fermented food produced by Bacillus subtilis natto ( B. subtilis natto), is widely consumed around the world, and its potential health functions are attracting attention. Natto has been reported to have a variety of bioactive compounds such as levan, menaquinone‐7, nattokinase, and others. Such bioactive compounds produced by B. subtilis natto are deeply involved in the function of natto, because they are consequently contained in natto. This review summarizes bioactive compounds and its functions of (1) B. subtilis and its subspecies, (2) B. subtilis natto. Overall, natto is a natural source of bioactive compounds and is expected to be applied to functional foods. Abstract : Natto, produced by fermentation of soybeans by B. subtilis natto (a subspecies of B. subtilis ), has been consumed as a traditional fermented food for at least a thousand years. Natto is attracting interest as a potential functional food for health. This review summarizes compounds and its functions of B. subtilis natto.